Introduction to management accounting - Horngren, Charles T.; Sundem, Gary L.; Burgstahler, David; Schatzberg, Jeff (Pearson, 2014)
Introduction to Management Accounting helps to enhance students' ability to make effective economic decisions by encouraging them to understand the inner-workings of the concepts, rather than solely focusing on technique memorization.